EFL Teachers’ Challenges and Insights of Online Teaching amidst Global Pandemic - Arif Nugroho; Dwi Ilmiani; Agnira Rekha (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
The unexpected shift of English language teaching from face-to-face classroom interaction to online learning activities using digital platforms has resulted in a number of challenges for English teachers and students. Hence, examining the teachers’ challenges and their insights of the online learning activities is highly required. The present study sheds some light on university EFL teachers’ challenges and insights of online learning activities amidst global pandemic. Drawing on the data collected using self-written reflections and semi-structured interviews from 17 Indonesian EFL teachers, the results revealed that the absence of an e-learning platform, lack of students’ motivation and engagement, and time consuming to prepare online learning materials became the primary challenges of the teachers. The results further portrayed that developing a representative digital platform, designing online learning materials, and improving the quality of teaching method were several valuable insights from the teachers. The results of this study contribute to providing fruitful advices for English teachers, students, and school authorities to enhance the efficacy of online teaching and learning activities, particularly during the global pandemic.